Edukasi Pencegahan Hipertensi pada Usia Produktif - Irianto, Irni Dwiastiti; Aisyah, Siti; Nufus, Lale Syifaun; Sulastien, Herni; Zulfa, Eva; Megawati, Jamila Purnama Sari (Idea Pengabdian Masyarakat, 2023)
Hypertension is a condition of systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg. Prevention of hypertension can be done by controlling a healthy lifestyle including controlling sleep habits, eating habits, weight control, not smoking or drinking alcoholic beverages, exercising exercise regularly and can manage stress. The purpose of this service is to provide education on prevention of hypertension at a productive age for prevention of hypertension in the hope of reducing morbidity due to hypertension in the community. The method used is education, discussion, distribution of leaflets regarding hypertension material, the implementation of this service is carried out through several stages, namely direct measurement of blood pressure, implementation of education and distribution of leaflets. The number of participants in the extension was 25 people. The results obtained during the community trial show that people of productive age know what precautions can be taken to prevent hypertension. It is hoped that this community service activity will continue.